Passivity-based controller for chemical processes - Camacho, Osear; Rojas, Rubén; Pernía Espinoza, Alpha; Pérez de la Parte, Mercedes (Rev. Téc. Fac. Ing. Univ. Zulia)
This paper presents the development of a Passivity -Based Controller (PBCr) from a Firsl-OrderPlus-Dead-Time model of the process. This approach results in a fixed structure controller that depends on the characteristic parameters of the model. This allows a unique controller of adjustable parameters that can be used in several processes. Computer simulations on a nonlinear chemical process judge the controller performance. The simulation results showed effectiveness and good performance for the studied case.